Uji Kualitas Batuan Sebagai Bahan Dasar Konstruksi Bangunan, Desa Balean & Sekitarnya, Kecamatan Lobu, Sulawesi Tengah - Latingara, Fahrul; Arifin, Yayu Indriati; Kasim, Muhamad; Aris, Ayub Pratama (Universitas Negeri Gorontalo, 2025)
One of the natural resources commonly utilized as raw material in industries—particularly for piling foundations, construction base mixtures, and other basic building materials—is igneous rock. The quality of the rock used as a construction material plays a crucial role in determining its suitability for various infrastructure applications. Therefore, specific physical and mechanical properties of the rock must be evaluated to assess its feasibility for construction use (Yuwanto and Araujo, 2020). This study aims to analyze the characteristics and quality of the rock at the research site and assess its suitability based on the classification from the Indonesian Industrial Standard (SII) 0378-80. The methods used include the Geological Strength Index (GSI) and Unconfined Compressive Strength (UCS). Data were obtained from field observations using the scan line method and laboratory testing of rock mechanical properties. The GSI analysis shows that the rocks have Structure Condition Rating (SCR) values of 6, 10, and 7, indicating structural influence ranging from blocky/disturbed to disintegrated conditions. The UCS analysis results show compressive strength values ranging from 233.351 kg/cm² to 1.161 kg/cm². According to the SII 0378-80 classification, these values reflect the varying levels of suitability of the rock for construction purposes.